IN SILICO STUDY OF ESTRAGOLE, APIOLE AND MYRISTICIN FROM Nigella sativa L. AS ANTIFUNGAL - Nurman, Nurman; Amrullah, Syarif Hidayat; Dirhamzah, Dirhamzah (Borneo Journal of Biology Education (BJBE), 2024)
Black cumin (Nigella sativa L.) is a plant that is widely used in world medicine. This is due to the large amount of chemical compounds that can have a positive effect on the body. Therefore, this study wants to see the potential use of chemical compounds from black cumin from the phenyl propanoid compounds, namely estragole, apiole and myristicin. Reverse docking study was perfomed using PyMOL Software v1.7.4.5 (Schrodinger), PyRx 0,8 software, SwissAdme Prediction and Discovery study 2019 client. The results of this study indicate that Myristicin can be a new drug candidate for anti-fungal based on the binding affinity value, namely -8.7 and close to the binding affinity value of e (a compound that is widely used as an anti-fungal).